Utilization of host proteins by human and feline coronaviruses - Zabiegala, Alexandria (My University, 2026)
Coronaviruses are important pathogens capable of infecting a wide range of species. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was the etiologic agent responsible for the COVID-19 pandemic, and cross-species transmission of SARS-CoV-2 was observed in a variety of species, mounting concern for animal reservoirs. Using lentivirus-based pseudoviruses carrying the spike protein (S) of SARS-CoV-2 parental and Omicron variants, we transduced CRFK cells stably expressing ACE2 of various species including dog, cat, mink, and white-tailed deer to assess entry potential. We found that pseudotyped viruses carrying S of the various SARS-CoV-2 Omicron strains efficiently entered cells expressing human or animal ACE2 comparably or better than those with parental strain. Host proteases also play an important role in coronavirus cell entry through proteolytic processing of S. Using the pseudoviruses carrying S from SARS-CoV-2 strains as well as SARS-CoV and Middle Eastern respiratory syndrome coronavirus (MERS-CoV), we assessed host proteases on virus entry and S cleavages using western blotting, entry/inhibition assays, and fusion assays. The presence of TMPRSS2 significantly increased the entry of all tested pseudoviruses and correlated with S cleavages and fusion events. The results suggest the importance of continual evaluation of SARS-CoV-2 variants in their susceptibility to animal species through ACE2, and comparable analysis of entry efficacies of SARS-CoV-2, SARS-CoV and MERS-CoV provide details of entry processes with host proteases among different coronaviruses. Feline infectious peritonitis (FIP) is a fatal systemic disease of cats, which is caused by FIP virus (FIPV). Viral mutation and host factors including T cell immunity play critical roles in the development of FIP. Because the PD-1/PD-L1 axis is a major target for viral evasion mechanism against T cell immunity, we assessed the expression of PD-L1 in cells infected with various strains of FIPV along with the subclinical biotype feline enteric coronavirus (FECV). While both viruses demonstrated robust viral replication at comparable levels, FIPV-1146, but not FECV-1683, significantly upregulated PD-L1 expression in two cell lines. We also assessed the PD-L1 expression in tissues of cats naturally infected with FIPV. PD-L1 mRNA levels in relation to viral load were highly variable among tissues and cats. On confocal microscopy, we found that PD-L1 and FCoV expression were clustered and largely co-localized in the tissues. These findings support further investigation into the role of PD-L1 and T cell responses in the development of FIP.
Keywords: Coronavirus; PD-L1; Proteases